Contemporary studies on modern Chinese history I - Zeng, Yeying; Li, Wenzhong; Wu, Jinshan (London : Routledge, 2021)
The study of modern Chinese history has developed rapidly in recent decades and has seen increased exploration of new topics and innovative approaches. Resulting from a special issue of Modern Chinese History Studies, this volume is devoted to showcasing the healthy development of Chinese modern history studies, and has already been revised twice in the original language. This volume exhibits major achievements on the study of modern Chinese history and shows how the role of history was in debate, transformation and re-evaluation throughout this tortuous yet prosperous period. Articles on eight different topics are collected from 11 prominent historians in order to represent their insights on the developmental paths of Chinese historical studies. Drawing on a large number of case studies of critical historical events, such as the founding of the Communist Party of China and the May 4th Movement, this volume reflects on economic history and military history, while moving on to explore more pioneering topics such as intellectual history and cultural history. This book will be a valuable reference for scholars and students of Chinese history.
1 An Overview ZENG Yeying 2 Theories and Methods ZHANG Haipeng 3 The Political History of the Late Qing Dynasty ZENG Yeying and JIANG Tao 4 A History of the Republic of China WANG Chaoguang 5 Economic History YU Heping 6 Military History LIU Tong and MAO Haijian 7 Intellectual History GONG Shuduo, DONG Guicheng and QIU Tao 8 Studies on Cultural History LIU Zhiqin
OCLC-licensed vendor bibliographic record.
Keywords: China -- Historiography; HISTORY / General; HISTORY / Asia / China; HISTORY / Modern / 20th Century